The mystery at Skeleton Point - Warner, Gertrude Chandler, 1890-1979.; Tang, Charles (Morton Grove, Ill. : A. Whitman, 2002)
The Boxcar Children help out a friend of their grandfathers fix up the mansion she just bought. The house is filled with skeletons and valuable statutes start disappearing.
Accelerated Reader AR
Keywords: Brothers and sisters -- Fiction; Orphans -- Fiction; Mystery and detective stories; Skeletons -- Fiction